2015
DOI: 10.4236/aim.2015.510074
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Profiles among <i>Escherichia coli</i> Strains Isolated from Athi River Water in Machakos County, Kenya

Abstract: Antimicrobial use in agriculture, livestock and human health has increased over the years leading to the increase in antimicrobial resistance that can also find its way to the aquatic environment. Rivers can act as reservoirs of highly resistant strains and facilitate the dissemination of multidrug resistant (MDR) strains to animals and humans using water. A total of 318 water samples were collected from six different sampling points along Athi River and E. coli isolates were subjected to Kirby-Bauer diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
4
8
1
Order By: Relevance
“…Isolates in dry season were higher than the wet season. These observations differed from those obtained in previous similar studies [27].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Isolates in dry season were higher than the wet season. These observations differed from those obtained in previous similar studies [27].…”
Section: Discussioncontrasting
confidence: 99%
“…The current study also reported high number of resistant bacteria especially for ampicillin, amoxicillin, ceftazidime, cefotaxime, cefepime. These results are close to those published in related studies conducted in [27]. This is a public health concern because increase in resistant bacteria may complicate treatment of infections arising from such strains.…”
Section: Discussionsupporting
confidence: 88%
“…to multiple antibiotics. Our findings were similar to those obtained by Wambugu et al [42] in Escherichia coli strains isolated from different sections of Athi River Water (Kenya). Such resistance was also shown by Fanuncio and Nuñeza [39] in Escherichia coli strains isolated from water hand pumps (Philippines).…”
Section: Antibiotic Resistance Testsupporting
confidence: 93%
“…Escherichia coli was discovered by Theodor Escherich in 1885. It is a gram-negative bacillary bacterium, commonly found in the intestines of humans and animals, and is an important indicator of water, soil and food contamination (Wambugu et al, 2015;Osinska et al, 2017). The wide use of antimicrobials in the fight against infectious diseases results in a continuous release of these drugs into waters and soils (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%